2015
DOI: 10.1080/15548627.2015.1023983
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of cilia and autophagy via the MTOR and proteasome pathways

Abstract: Abbreviations: 3-MA, 3-methyladenine; ANKS6, ankyrin repeat and sterile a motif domain containing 6; ATG/atg, autophagy-related; Baf, bafilomycin A 1 ; DAPI, 4 0 -6-diamidino-2-phenylindole; Ac-TUBA, acetylated-tubulin a; CQ, chloroquine; CF, confluence; FBS, fetal bovine serum; HK2, human kidney proximal tubular cells; IFT, intraflagellar transport; K D , knockdown; KAP3, kinesin family-associated protein 3; KIF3A/3B, kinesin family member 3A/3B; KO, knockout; MAP1LC3B/LC3B, microtubule-associated protein 1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 51 publications
10
95
1
1
Order By: Relevance
“…For example, the transcription factor, signal transducer and activator of transcription 1 (STAT1), and MAPK8 (JUNK1) are present in cysts and can potentially mediate cell death by apoptosis or necrosis, and autophagy 127,128 . A recent study has further demonstrated a reciprocal regulation between cilia and autophagy 129 . Essentially, the cells with shorter cilia had lower levels of autophagy and, conversely, inhibition of autophagy reduced cilia growth.…”
Section: Introductionmentioning
confidence: 94%
“…For example, the transcription factor, signal transducer and activator of transcription 1 (STAT1), and MAPK8 (JUNK1) are present in cysts and can potentially mediate cell death by apoptosis or necrosis, and autophagy 127,128 . A recent study has further demonstrated a reciprocal regulation between cilia and autophagy 129 . Essentially, the cells with shorter cilia had lower levels of autophagy and, conversely, inhibition of autophagy reduced cilia growth.…”
Section: Introductionmentioning
confidence: 94%
“…Thus, recent studies in a paradigm of kidney epithelial cell differentiation have demonstrated a positive regulatory effect of ciliogenesis on basal autophagy [25]. In this context, the decreased basal autophagy resulting from a block in ciliogenesis can be restored by suppressing mTOR signaling, a well-characterized endogenous repressor of autophagy [25], whereas a similar intervention cannot overcome the defect in starvation-induced autophagy in fibroblasts lacking PC [15]. These divergences suggest that the mechanisms behind cilia-mediated autophagy are stimulus- and/or cell type dependent and could originate from a diversification in the receptor composition of the ciliary membrane according to the cell type or cell conditions.…”
Section: The Primary Cilium Is Required For Autophagy Activationmentioning
confidence: 99%
“…Although the increase in autophagy observed with these drugs could be secondary to the longer PC or to their effect in other cellular process, the idea that autophagy could regulate PC length both at the level of growth or at the level of disassembly is attractive. Adding complexity to the autophagy/PC interplay, the consequences of autophagy inhibition on PC growth have been shown to be dependent in part on the ability of different cell types to engage proteasome degradation upon autophagy blockage, although the specific proteins targeted by the proteasome under these conditions are yet to be identified [25]. …”
Section: Autophagy Regulates Ciliogenesismentioning
confidence: 99%
“…The mammalian target of rapamycin complex‐1 (mTORC1) was recently identified as a regulator of renal Na + and K + handling, and has been reported to be involved in the control of cilium growth . We therefore assessed the effects of aldosterone of mTORC1 activation.…”
Section: Resultsmentioning
confidence: 99%